Circulating free DNA as a predictive biomarker for response to nivolumab and platinum-based chemotherapy in metastatic esophageal adenocarcinoma: a prospective pilot study - Du, Qing Sheng; Fan, Bo (Frontiers in Oncology, 2025)
BackgroundReliable biomarkers are urgently needed to predict response to immune checkpoint inhibitors in metastatic esophageal adenocarcinoma (mEAC). This study evaluated early circulating free DNA (cfDNA) dynamics as a predictor of treatment response and survival in patients receiving platinum-based chemotherapy plus Nivolumab.MethodsIn this prospective pilot study, 95 patients with mEAC were treated with Nivolumab and platinum-based chemotherapy. Plasma cfDNA levels were measured at baseline, Day 15, and Day 30 using digital droplet PCR. The primary outcome was objective treatment response; secondary outcomes included progression-free survival (PFS) and overall survival (OS). Tumor mutational burden (TMB), PD-L1 expression, liver metastasis, and ECOG status were also assessed.ResultsPatients with a cfDNA Day 30/Baseline ratio <0.4 had significantly improved median PFS (11 vs. 4 months) and OS (14 vs. 7 months) compared to those with ratios >0.8 (p for trend <0.001). Early decline in cfDNA correlated with treatment response. High TMB (≥10 mut/Mb) was independently associated with increased response (adjusted OR: 2.5, 95% CI: 1.2–5.2, p=0.015). ECOG >1 was inversely associated with response (adjusted OR: 0.35, p=0.01). PD-L1 expression and liver metastasis were not significantly predictive.ConclusionEarly cfDNA kinetics—particularly a Day 30/Baseline ratio <0.4—strongly predicted response and survival in mEAC patients receiving chemoimmunotherapy. cfDNA monitoring offers a promising non-invasive tool for early treatment stratification and response assessment in this population.